Evaluation of acellular pertussis vaccine: comparisons among different strains of mice - Jie Wei; Jiaona Guang; Chen Wei; Hong Wang; Jiaqi Zhou; Huan Li; Lichan Wang; Xiao Ma; Bingfei Yue (Emerging Microbes and Infections)
The current study was designed to comparatively analyse the reactions of different mouse strains in response to acellular pertussis (aP) vaccine, with attempt to further provide a reference for aP vaccine evaluation. NIH mice, ICR mice, and BALB/c mice adopted from different pharmacopoeias and studies were utilized to measure the immune protection and immunogenicity of the same batch of aP vaccine according to the Modified intracerebral challenge assay (MICA) from some Asian pharmacopoeias and the pertussis serological potency test (PTST) method from European Pharmacopoeia. Based on our results, the aP vaccine detected by NIH mice had the best potency. So the NIH mice were more suitable for detecting the immune protection of aP vaccine by the MICA method. Given that the levels of PT-IgG and FHA-IgG antibodies in ICR mice were the highest, and the levels of Th1 and Th2 cells were significantly increased (P < .01), it was more suitable for the detection of immunogenicity of aP vaccine by PSPT method. Spleen lymphocytes were stimulated by PT and FHA. And the levels of IL-4 in ICR mice and NIH mice were significantly increased, so were the levels of IL-17, IL-23, IL-27, and TNF-α in BALB/c mice. NIH mice have stronger adaptive immunity and the weakest inflammatory response, and ICR mice have enhanced adaptive immunity and inflammatory responses, both of which can be thereby used for evaluation by different pharmacopoeia methods. NIH was more suitable for the MICA method of Chinese Pharmacopoeia, and ICR for the PSPT method of European Pharmacopoeia.